(untitled) (Journal of the College of Basic Education, 2022)
Multimedia is a kind of technological teaching aids that can be applied during the teaching and learning process. It is a combination of sounds, graphics, animation and video. In the world of computers, it is a part of hypermedia, which connects the elements of multimedia with hypertext for the purpose of creating links among pieces of information. Therefore, these techniques are expected to deal with vocabulary and pronunciation difficulties of Iraqi EFL students especially at the primary school ones in order to reduce the mistakes in pronunciation and to enhance their vocabulary repertoire. The present study aims at investigating the effect of using multimedia techniques on Iraqi EFL learners’ performance in vocabulary and pronunciation. For this purpose, it is hypothesized that there is no statistically significant difference between the mean score of the students who are taught vocabulary and pronunciation using multimedia techniques, and that of those who are taught vocabulary and pronunciation using strategies that are recommended in the prescribed textbook.